FAIRY TALES SYMBOLS REFLECTED IN SHARON MAGUIRE GODMOTHERED MOVIE (2020) - Ferlin Setiasih; Abdur Rofik (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2022)
This research is conducted to analyze fairy tales symbols presented in Sharon Maguire Godmothered movie (2020) and the semiotic analyzes of fairy tales’ symbols in Godmothered movie (2020). There are two problem statements that the researcher used in this research, first, what are the fairy tales symbols presented in Godmothered movie (2020)? Second, how are the fairy tales symbols revealed in Godmothered movie (2020)? The researcher used the qualitative method to examine the problem. The theory and approaches that the researcher used is Semiotic. This study also includes the procedures of collecting data and procedure of analyzing data. The results of this study, first, the fairy tales symbols shown through someone actions and dialogue, second, the meaning of the fairy tales signs can be analyzed by using triadic concept of Pierce’s semiotic theory. The types of symbols are more than one, depend on the symbol’s category type.